English for international tourism : - Cowper, Anna (Pearson Education Limited, 2013)
English for International Tourism is a three-level series designed to meet the English-language needs of professionals working in the tourism industry and students of tourism in further education. The course includes authentic material taken from the world’s best-loved guidebooks, Dorling Kindersley’s Eyewitness Travel Guides which explore some of the world's top tourist destinations. English for International Tourism Workbook with key offers a wide variety of practice and review exercices and covers all of the language areas studied in the unit. With audio CD including all the audio material of the workbook.